The effect of the make a match learning model assisted by picture card media on students' cognitive learning outcomes in the human respiratory system topic - Dewi, Feby Firmilia; Nasution, Nanda Eska Anugrah; Rizka, Chairany (Univeritas Papua, 2025)
Biology education is essential for enhancing students' comprehension of intricate scientific topics and their practical applications. However, conventional teacher-centered approaches at MAN 2 Probolinggo City have led to diminished student involvement and inadequate cognitive learning outcomes, especially for the human respiratory system topic. This study aimed to assess the effectiveness of the Make a Match learning model, supplemented with picture card media, in enhancing cognitive learning outcomes for 11th grade students. A quasi-experimental design with a posttest-only approach was employed, involving 36 students in the experimental group and 36 in the control group, where both groups had equivalent initial learning outcomes based on their teacher-assigned scores. Independent sample t-test results showed a statistically significant improvement in the experimental group (M=89.11,SD=6.093) compared to the control group (M=83.78,SD=6.339), p=0.001. The Make a Match model enhanced by the use of picture card media promoted active engagement, collaboration, and visual learning, with the visual representations of respiratory organs and their functions significantly aiding comprehension of the system's intricate concepts. The findings highlight the model's potential as a dynamic instructional method that can improve cognitive learning outcomes.